The Tolerogenic Function of Regulatory T Cells in Pregnancy and Cancer - Jørgensen, Nanna; Persson, Gry; Hviid, Thomas Vauvert F. (Frontiers in Immunology, 2019)
Regulatory T cells, a subpopulation of suppressive T cells, are potent mediators of self-tolerance and essential for the suppression of triggered immune responses. The immune modulating capacity of these cells play a major role in both transplantation, autoimmune disease, allergy, cancer and pregnancy. During pregnancy, low numbers of regulatory T cells are associated with pregnancy failure and pregnancy complications such as pre-eclampsia. On the other hand, in cancer, low numbers of immunosuppressive T cells are correlated with better prognosis. Hence, maternal immune tolerance toward the fetus during pregnancy and the escape from host immunosurveillance by cancer seem to be based on similar immunological mechanisms being highly dependent on the balance between immune activation and suppression. As regulatory T cells hold a crucial role in several biological processes, they may also be promising subjects for therapeutic use. Especially in the field of cancer, cell therapy and checkpoint inhibitors have demonstrated that immune-based therapies have a very promising potential in treatment of human malignancies. However, these therapies are often accompanied by adverse autoimmune side effects. Therefore, expanding the knowledge to recognize the complexities of immune regulation pathways shared across different immunological scenarios is extremely important in order to improve and develop new strategies for immune-based therapy. The intent of this review is to highlight the functional characteristics of regulatory T cells in the context of mechanisms of immune regulation in pregnancy and cancer, and how manipulation of these mechanisms potentially may improve therapeutic options.